Cholic acid-modified polyethylenimine: in vitro and in vivo studies - Dube B (Dove Medical Press, 2018)
Brahmanand Dube,1,2 Abhijeet Pandey,1 Ganesh Joshi,3 Rita Mulherkar,3 Krutika Sawant1 1Pharmacy Department, Faculty of Pharmacy, The Maharaja Sayajirao University of Baroda, Vadodara, 2Wockhardt Research Centre, Wockhardt Ltd, Aurangabad, India; 3Genetic Engineering Laboratory, ACTREC Tata Memorial Centre, Kharghar, Navi Mumbai Abstract: Low-molecular-weight polyethylenimine has lower cytotoxicity than high molecular weight polyethylenimine, but it is not an efficient transfection agent because of limitations of DNA delivery into the cytoplasm. Therefore, in the present study, the hydrophobic modification of low-molecular-weight polyethylenimine (PEI 2 kDa [PEI2]) by cholic acid (ChA) was performed to form PEI2-ChA, and in vitro and in vivo studies were performed. Results indicate that the nanoplexes of PEI2-ChA with gWIZ-GFP have greater transfection efficiency (27%) in NT8e cell lines as evaluated by flow cytometry and also observed by fluorescence imaging. The present study concluded that the transferrin-containing nanoplexes of PEI2-ChA conjugates with plasmid p53 warrant clinical trials in humans after exhaustive animal studies for use as a novel gene delivery system. Keywords: polyethylenimine, biodistribution, tumor regression